Julia Kristeva - McAfee, Noëlle (Routledge critical thinkers, 2004)
"One of the most original thinkers of our time, Julia Kristeva has been a leading force in the fields of literary and cultural studies, psychoanalysis, semiotics, feminist theory, and philosophy. This book gives a lively and lucid account of Kristeva's most important ideas, including her concepts of the semiotic and symbolic, abjection, melancholia, and revolt. Noelle McAfee provides clear explanations of the more difficult aspects of Kristeva's work, helpfully placing her ideas in the relevant theoretical contexts, and examining their impact on literary studies and critical theory." "Julia Kristeva is the essential guide for readers who are approaching the work of this challenging thinker for the first time and it provides the ideal opportunity for those with more knowledge to re-familiarize themselves with Kristeva's key terms."--BOOK JACKET.